HAKIKAT MAHA LEMBUT TUHAN DALAM AL-QUR’AN DAN ALKITAB - Ebin, Muhammad Ebin Rajab Sihombing (Universitas Muhammadiyah Surabaya, 2024)
This article attempts to outline certain concepts from the Qur'an and the Bible that discuss God's tenderness. God's gentleness is not just a concept; he love reflects His infinite compassion, wisdom, and forgiveness. An important aspect in this study, apart from knowing the nature of God's Most Gentle nature from the perspective of the Koran and the Bible, is also to compare them using transcendence and immanence analysis. Through this cross-religious study, researchers will try to assemble a spiritual puzzle that connects Islamic and Christian teachings in understanding the nature of God, the Most Gentle. This research uses a qualitative comparative method. The study displays and explains the verses in which there is an explanation of the gentle nature of God. Then these verses are discussed with the transcendence and immanence of Thomas Aquinas. This research found that in the Qur'an, the transcendence of the Most Gentle God shows that Allah goes beyond the limits of human understanding, while His gentleness is reflected in events such as the translation of the Prophet Yusuf. On the other hand, the Bible highlights Jesus' transcendence through prophecies and God's plans that humans do not fully understand, especially in His coming that does not match worldly expectations. Meanwhile, immanence highlights His tenderness that permeates and is involved in every aspect of life. Even though there are differences, similarities still exist in the image of God who is Most Gentle in giving teachings, providing sustenance, and being involved in human life.